Caffeine increases vertical jumping height in young trained males before but not after a maximal effort strength training session - Tangen, D. S.; Nielsen, S. R.; Kolnes, K. J.; Jensen, J. (Journal of Science in Sport and Exercise, 2020)
The aim of the present study was to investigate the effect of caffeine on vertical jumping height in rested condition and after a heavy strength training session. Six well-trained young males with experience in jump and strength training were included in this double-blinded, randomised study with cross-over design. Caffeine (3 mg/kg body weight) or placebo were ingested 45 min prior to the jump tests. Jumping was performed on a force platform and vertical jumping height was calculated. After a standardized warm up, participants performed jumping series consisting of three maximal jumps with 30 s rest between jumps followed by five maximal jumps with 7 s rest between jumps. The participants performed a heavy strength training of the leg muscles (leg press: 3 × 15 reps) and the jumping series was repeated immediately after (30 s), and after 5 min and 15 min recovery. Caffeine increased the maximal vertical counter movement jump height (P = 0.05) and mean value of the 5-jump sequence prior to the strength training. Caffeine increased jump height by 2.2 cm ± 0.5 cm at the first jump. Blood lactate after the strength training increased to 6.97 ± 1.20 and 7.77 ± 0.54 mmol/L in PLA and CAF, respectively (P = 0.19). The jump height was reduced by 8 cm after the strength training. There were no differences in jump height after ingestion of caffeine or placebo immediately after the strength training session or in the recovery period, but blood lactate in the recovery period was higher in CAF compared to PLA (ANOVA; P < 0.05). Conclusion: Caffeine increased the vertical jump height in the resting state. However, after a maximal effort strength training session the positive effect of caffeine was no longer significant.